Aux détours de la vie d’Augustin Meaulnes et de Gaspard Fontarelle, le devenir de l’Homme - Maria Eugénia Pereira (Carnets)
The heroes of Grand Meaulnes and of Pays où l’on n’arrive jamais are invaded by a spirit of childhood and therefore cannot stand the world as it presents itself. In a deep angst, they through themselves into mysterious and unknown lands in their desire to access the elusive. Alain-Fournier and André Dhôtel therefore invite us to discover a different world, where magic is integrated into reality. We enter it without questioning, accepting the unusual and detaching ourselves from everyday life and the mundane through the childhood imagination that has remained with us.